Computer Simulations Applied to Small-Field Dosimetry in Radiotherapy (Brazilian Journal of Radiation Sciences (BJRS), 2022)
With the advancement of radiotherapy techniques, we find some challenges in small field dosimetry that are widely used in head and neck treatments, so computer simulations with the Monte Carlo method, already well established in medical physics, are a great tool for  studying small field dosimetry. The present work aims to report the validate of the geometry model used for the simulations of a 6 MV LINAC beam, in addition to estimating the TPS, PDD and PDD 20,10 curves for several regular and small fields, allowing comparisons with experimental data .